Pemahaman Konsep Perkalian dengan Model Discovery Learning di Sekolah Dasar - Jarmita, Nida; Yunita, Irma; Rahmi, Putri (Jurnal keilmuan dan Kependidikan dasar, 2024)
This study aims to improve the understanding of multiplication concepts among second-grade students at SDN Lamklat Aceh. Therefore, the researcher applied a classroom action research (CAR) method using the Kemmis Mc. Taggart model, which consists of four stages: planning, acting, observing, and reflecting. The improvement action chosen was the Discovery Learning model. Data collection techniques included observation and tests., The researcher used a percentage formula for data analysis according to predetermined success criteria. The results showed that teacher activity in the first cycle achieved a percentage of 87.5%, in the second cycle, it increased to 98.7%. Student activity in the first cycle reached 75%, and in the second cycle, it rose to 92.6%. The percentage of students' mastery for the multiplication concept understanding test in the first cycle was 50.0%, and in the second cycle, it increased to 85.7%. Thus, it can be concluded that the use of the Discovery Learning model can improve the understanding of multiplication concepts among second-grade students at SDN Lamklat Aceh Besar